ANALISIS SOSIOLOGIS PERILAKU KONSUMTIF MAHASISWA (Studi pada Mahasiswa FISIP Universitas Lampung) - Aprilia, Dewi; Hartoyo, Hartoyo (JURNAL SOSIOLOGI, 2013)
This research aims to clarify the relationship between socio-economic status of the elderly and consumer behaviour with reference to groups of students. The research method used is the quantitative eksplanatoris. The technique of collecting data carried out through a questionnaire. The result showed that, first there are relations is being ( 0,544 ) between socioeconomic status in parents with the behavior consumptive student. It showed that the higher socioeconomic status in the old man and behavior consumptive students also increase. Second, there is a relationship is being ( 0,516 ) between socioeconomic status in the old man with the manners consumptive mahasiswa controlled with clusters of reference. It showed that a factor of socioeconomic status in the old man is not the only affecting high low-self behavior consumptive students, but also a group of reference by which can affect behavior consumptive students. Third, there was no correlation that means between socioeconomic status in parents with clusters of reference. So can be concluded that high low socioeconomic status in parents students have has huge against the influence exerted by group references in buying goods to be desired. Fourth, there is no relationship between consumer behaviour with reference to groups of students. In this case the students buy goods not because of the excessive influence exerted by the reference group.Â Keywords: socio-economic status of parents, groups of references and consumer behavior of university students